Electromyographic correlates of effortful listening in the vestigial auriculomotor system - Schroeer, Andreas; Corona-Strauss, Farah I.; Hannemann, Ronny; Hackley, Steven A.; Strauss, Daniel J. (Frontiers in Neuroscience, 2025)
Recently, electromyographic (EMG) signals of auricular muscles have been shown to be an indicator of spatial auditory attention in humans, based on a vestigial pinna-orienting system. Because spatial auditory attention in a competing speaker task is closely related to the more generalized concept of attentional effort in listening, the current study investigated the possibility that the EMG activity of auricular muscles could also reflect correlates of effortful listening in general. Twenty participants were recruited. EMG signals from the left and right superior and posterior auricular muscles (SAM, PAM) were recorded while participants attended a target podcast in a competing speaker paradigm. Three different conditions, each more difficult and requiring a higher amount of effortful listening, were generated by varying the number and pitch of distractor streams, as well as the signal-to-noise ratio. All audio streams were either presented from a loudspeaker placed in front of the participants (0°), or in the back (180°). Overall, averaged PAM activity was not affected by different levels of effortful listening, but was significantly larger when stimuli were presented from the back, as opposed to the front. Averaged SAM activity, however, was significantly larger in the most difficult condition, which required the largest amount of effort, compared to the easier conditions, but was not affected by stimulus direction. We interpret the increased SAM activity to be the response of the vestigial pinna–orienting system to an effortful stream segregation task.